Harmonização vocálica : frequência de uso das palavras - Carcuchinski, Caroline Narcizo (2017)
This dissertation aims at presenting a study about the frequency of use of vocal harmonization, a variable rule motivated by a high vowel in a immediately following syllable. Based on studies about Use Phonology, proposed by Bybee (1985, 2002, 2010), is presented here a comparative analyses over the role of the frequency in use of words of a particular bank and frequency in a bank of general data. The results converge when referred to the high frequency, but diverge when referred to low frequency. Is highlighted the role of frequency in terms of information related to the rule establishment in contemporary phonology of Portuguese.